MRI Enhancement Associated with TFCC and Scapholunate Interosseous Ligament Tears - Daunt, Nick; Ross, Mark; Couzens, Greg; Anderson, Libby; Curran, Matthew W.T. (Journal of Wrist Surgery, 2025)
Objective This study aimed to evaluate the appearance, timing, and pattern of enhancement on magnetic resonance imaging (MRI) associated with triangular fibrocartilage complex (TFCC) and scapholunate interosseous ligament (SLIL) tears.Materials and Methods A retrospective review of patients with TFCC and SLIL tears identified on MRI was conducted to determine patterns and timelines of enhancement after a gadolinium injection. The appearances were compared with the postcontrast appearances in a group of asymptomatic controls who presented with non-traumatic indications for MRI that required gadolinium contrast. Demographic data, including age, duration of symptoms, and mechanism of injury, was collected.Results Eighty-seven patients with enhancement following gadolinium injection were included in the study. Fifty patients with enhancing peripheral TFCC tears and 54 patients with SLIL tears that showed enhancement were identified from a search of MRI records. In the symptomatic TFCC injuries, all showed contrast enhancement associated with ulna-sided TFCC tears. Forty-four patients showed enhancement extending beyond the confines of the anatomical TFCC into the adjacent fat planes, particularly dorsal to the dorsal radioulnar ligament. For the SLIL, 53 of 54 showed enhancement in or replacing the volar band. In the control patients group, none showed any enhancement related to the TFCC or SLIL.Conclusion Intravenous gadolinium with postcontrast scans may help in diagnosing ulna-sided TFCC tears and SLIL tears. The pattern of enhancement may identify the extent of the tear and, for TFCC injuries possible involvement of the surrounding structures as well as demonstrating adjacent synovitis. These radiographic findings might be used to guide ultrasound-guided therapies and surgical management.
Keywords: carpal instability; magnetic resonance imaging; scapholunate ligament; TFCC; ulnar sided wrist pain; wrist injury